SPIROMETRIC EVALUATION PRE AND POST HEMODIALYSIS TREATMENT (Fiep Bulletin - online, 2017)
This study aimed to compare spirometry measurements before and after hemodialysis treatment. It was aquantitative and descriptive study in a foundation for treatment of people with chronic kidney disease. Data were analyzed usingsimple descriptive statistics and comparative through the Student t test. The study included 55 people with an average age of55,616,07 years. The average value obtained from the forced vital capacity, forced expiratory volume in one second, index ofTiffeneau and peak expiratory flow was pre hemodialysis 4,47L, 2,67L, 62,49% and 4,98L/s respectively. And after hemodialysiswas 4,56L, 2,73L, 62,04% and 4,66L/s, respectively. The mean forced vital capacity and forced expiratory volume in one secondincreased after hemodialysis and index of Tiffeneau and peak expiratory flow decreased. All variables compared statistically nosignificant difference. It was found in this study that after hemodialysis there was improvement in lung function and reversibility oflung disease in post hemodialysis.